Die andere Seite Chinas: Strukturprobleme, Reformdefizite und verzögerte Aufholprozesse im chinesischen Binnenland - Martin Raiser; Peter Nunnenkamp (Kiel Institute of World Economics (IfW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 1997)
The success of economic reforms in China is often attributed to favourable starting conditions. Yet structural characteristics and the effects of fiscal decentralisation differ significantly between the prosperous coast and the laggard interior. We argue that the process of income convergence has been uneven both over time and across provinces. Structural legacies and insufficient reform efforts are shown to have worked against enterprise efficiency and economic growth in China's hinterland. We conclude that, particularly, the System of regional transfers needs to be revised, in order to encourage adjustment at the firm level and provide poor provinces with better opportunities for catching up.
Keywords: D24; H71; O40; 330; Wirtschaftsreform; Regionale Disparität; Finanzausgleich; Reorganisation; Produktivität; Wirtschaftliche Effizienz; Hinterland; China